Steric Effects on the Thermal Processes of Hemithioindigo Based Molecular Motor Rotation - Huber, Ludwig A.; Thumser, Stefan; Grill, Kerstin; Voßiek, David; Bach, Nicolai; Mayer, Peter; Dube, Henry (Chemistry - A European Journal, 2021)
Tuning the thermal behavior of light driven molecular motors is fundamentally important for their future rational design. In many molecular motors thermal ratcheting steps are comprised of helicity inversions, energetically stabilizing the initial photoproducts. In this work we investigated a series of five hemithioindigo (HTI) based molecular motors to reveal the influence of steric hindrance in close proximity to the rotation axle on this process. Applying a high yielding synthetic procedure, we synthesized constitutional isomeric derivatives to distinguish between substitution effects at the aromatic and aliphatic position on the rotor fragment. The kinetics of thermal helix inversions were elucidated using low temperature 1H NMR spectroscopy and an in situ irradiation technique. In combination with a detailed theoretical description, a comparative analysis of substituent effects on the thermal helix inversions of the rotation cycle is now possible. Such deeper understanding of the rotational cycle of HTI molecular motors is essential for speed regulation and future applications of visible light triggered nanomachines.
CRIS-Team Scopus Importer:2021-06-11
Keywords: ground states; hemithioindigo; molecular motors; photochemistry; rotation mechanisms